Near-infrared NIR-IIb region light-emitting and temperature-measuring nano composite material as well as preparation method and application thereof

By preparing core-shell structured rare earth nanocomposites and utilizing the bidirectional response characteristics of emission peak intensity, the problem of low thermal sensitivity in NIR-IIb temperature measurement was solved, and high-precision deep tissue temperature detection was achieved.

CN120843082APending Publication Date: 2025-10-28SHANGHAI TECH UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511005354.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-21
Publication Date
2025-10-28

AI Technical Summary

Technical Problem

In existing technologies, the luminescent nanothermometry technology using rare earth-doped nanoparticles has low thermal sensitivity in the NIR-IIb region, making it difficult to achieve high-precision deep tissue temperature detection.

Method used

A near-infrared (NIR)-IIb region luminescence and temperature measurement nanocomposite material was designed. It adopts a composite structure of rare earth nanoparticles and distearate phosphatidylethanolamine-polyethylene glycol. The core-shell structured nanoparticles were prepared by a solvothermal method. The emission peaks are located at 980 nm and 1550 nm. The temperature measurement was performed by utilizing the bidirectional response characteristics of the emission peak intensity.

Benefits of technology

High-sensitivity temperature detection in the NIR-IIb region was achieved, with a relative sensitivity of 3%℃-1, which significantly improved the resolution of deep tissue imaging and the accuracy of temperature measurement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005510174160000151
    Figure BDA0005510174160000151
  • Figure HDA0005510174170000011
    Figure HDA0005510174170000011
  • Figure HDA0005510174170000021
    Figure HDA0005510174170000021
Patent Text Reader

Abstract

The invention discloses a nano composite material for emitting light and measuring temperature in a near-infrared NIR-IIb region as well as a preparation method and application of the nano composite material. Raw materials of the composite material comprise rare earth nanoparticles and distearoyl phosphatidyl ethanolamine-polyethylene glycol, the rare earth nanoparticles comprise a core layer and a shell layer coating the core layer, the structural general formula of the core layer is NaEr1-ATmAF4, the structural general formula of the shell layer is NaLuF4, and A is larger than or equal to 0 and smaller than or equal to 0.1. The nano composite material disclosed by the invention is high in temperature measurement repeatability and good in temperature measurement stability, a luminescence emission peak is positioned in an optimal imaging region (NIR-IIb), and the imaging resolution of deep tissues can be remarkably enhanced. Therefore, the composite material disclosed by the invention becomes an ideal material for promoting the development of a living body deep tissue high-precision temperature measurement imaging technology based on the unique luminescence characteristic and stable temperature measurement performance, and has huge application potential in the fields of biomedical imaging and temperature measurement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of materials technology, and in particular to a nanocomposite material for near-infrared (NIR)-IIb region luminescence and thermometry, its preparation method, and its applications. Background Technology

[0002] Temperature is a crucial parameter reflecting the normal physiological behavior of organisms. For example, the expression of specific genes, enzyme-mediated biochemical reactions, and the regulation of cell differentiation are all temperature-related. Furthermore, the metabolic rate of early-stage tumor cells is significantly higher than that of normal tissue cells, leading to an abnormal increase in the temperature of the local lesion environment. Therefore, cancer can be diagnosed through microscopic temperature detection. In photothermal therapy for cancer, precise detection of microscopic temperature changes can minimize thermal damage to surrounding normal cells while ensuring the killing of tumor cells. Therefore, accurate detection of microscopic temperature changes in specific regions of an organism is highly helpful for studying specific physiological processes and for more effectively tailoring treatment plans.

[0003] Current temperature measurement methods can be categorized into invasive and non-invasive types based on their invasiveness. Thermocouples and thermistors are widely used in temperature detection due to their cost-effectiveness and ease of use; however, they are invasive and difficult to use for micrometer-level temperature detection. Infrared thermal imaging provides a non-invasive temperature measurement technique that can acquire surface temperature information of an object in real time through two-dimensional thermal imaging, but it cannot obtain internal temperature data of materials. Magnetic resonance thermometry can perform non-invasive, high-precision in-situ observation of deep tissues, but the equipment is expensive, and temperature readings are easily affected by adipose tissue and motion artifacts. In the past decade, the scientific community has witnessed the rapid development of luminescent nanothermometry, which has also shown significant advantages in the biomedical field and has been demonstrated for early tumor diagnosis, precise cancer treatment, and minimally invasive brain temperature monitoring. Luminescent nanothermometry is based on the dynamics at the molecular, atomic, and even electronic scales, which exhibit temperature-responsive optical properties on a macroscopic scale. Currently, the mainstream luminescent nanothermometry technology is based on the intensity ratio thermometry of two different emission peaks. This method can monitor microscopic temperature changes in real time, and after correcting for interference caused by fluctuations in the immune environment through in vitro temperature readings, it can accurately reflect the internal temperature of living tissues.

[0004] In recent years, luminescent nanothermometry has made significant progress in the near-infrared (NIR) spectral region, particularly in the study of rare-earth-doped nanoparticles (LM-NPs). NIR is typically divided into two main regions based on emission peak range: NIR-I (700-900 nm) and NIR-II (1000-1700 nm); the NIR-II region is further subdivided into two sub-regions: NIR-IIa (1000-1300 nm) and NIR-IIb (1500-1700 nm). Rare-earth-doped nanoparticles (LM-NPs) exhibit temperature-dependent luminescence properties, with their excitation and emission wavelengths primarily located in the NIR region (e.g., excitation at 980 nm, emission at 800-1000 nm), making them highly promising for biomedical applications. Lanthanide-doped luminescent nanomaterials are ideal materials for designing optical nanoscale temperature probes due to their excellent optical stability, lack of scintillation and photobleaching, and tunable multicolor emission bands. For example, CN113930235 B discloses a multi-response nanoscale temperature detection probe, its preparation method, and its application, with the structural formula NaGd 0.5 Yb 0.49 Tm 0.01 F4@NaY 0.8 Yb 0.2 F4@NaGd 0.65 Yb 0.1 Nd 0.25 F4@NaGdF4, from the inside out, consists of the first layer of NaGd. 0.5 Yb 0.49 Tm 0.01 F4, Second Layer NaY 0.8 Yb 0.2 F4, Third layer NaGd 0.65 Yb 0.1 Nd 0.25 This probe has a four-layer structure consisting of F4 and a fourth layer of NaGdF4. Under 700-1000nm laser excitation, it can generate 1-3 near-infrared emission bands in the 1210-1500nm wavelength range, enabling the construction of 1-2 optical thermometers within the same system. The thermal sensitivity of these thermometers is between 0.6-1.3%℃. -1 However, the probe in this patent has a complex core-shell structure, which is complex to prepare, costly, and has low temperature sensitivity (S). r ≈1%℃ -1 Furthermore, its operating wavelength is not in the NIR-IIb region (1500-1700nm).

[0005] The master's thesis, "Construction and Application Research of Temperature Probes Based on Er / Tm Partitioned Doping," discloses NaErF4:0.5%Tm (Er:Tm) nanoparticles. The study discovered the relationship between the upconversion luminescence of NaErF4:0.5%Tm@NaYF4 and temperature, and investigated the effect of Er / Tm partitioned doping on temperature under extreme conditions (low-temperature field, operating temperature 100K). 3+ The temperature response behavior of upconversion emission at 654 nm and 540 nm was reported in this paper. However, Er was not reported in this paper. 3+ The temperature response behavior of the downtransfer luminescence, and whether the material can be used for in vivo thermometry, were investigated, and the relative sensitivity of the material at room temperature (300 K) was less than 0.15% °C. -1 It is far from meeting the design standards of temperature probes (S r ≈1%℃ -1 ).

[0006] In the field of bioimaging, the NIR-IIb region (1500-1700 nm) is widely recognized as the ideal optical imaging window due to its extremely low autofluorescence background signal and significantly reduced light scattering in biological tissues, resulting in image quality far superior to the visible light region (400-700 nm). Currently, rare-earth-doped nanotemperature probes with operating wavelengths in the NIR-IIb region (1500-1700 nm) are scarce and have low thermal sensitivity. Therefore, there is an urgent need to develop luminescent nanocomposite materials with operating wavelengths (i.e., emission peaks) in the NIR-IIb region to advance the development of high-precision temperature imaging of deep tissues. Summary of the Invention

[0007] In view of the shortcomings of the prior art described above, the purpose of this invention is to provide a near-infrared (NIR)-IIb region luminescent and thermometric nanocomposite material, its preparation method and application.

[0008] To achieve the above and other related objectives, the present invention is obtained through the following technical solution.

[0009] The first aspect of this invention protects a nanocomposite material for near-infrared (NIR)-IIb region luminescence and thermometry. The raw materials of the composite material include rare earth nanoparticles and distearate phosphatidylethanolamine-polyethylene glycol. The rare earth nanoparticles comprise a core layer and a shell layer covering the core layer. The general structural formula of the core layer is NaEr. 1-A Tm A F4, the general structural formula of the shell is NaLuF4, where 0≤A≤0.1.

[0010] In some embodiments, the nanocomposite material exhibits a decrease in luminescence intensity at the emission peak of 980 nm with increasing temperature, and an increase in luminescence intensity at the emission peak of 1550 nm with increasing temperature.

[0011] In some embodiments, the mass ratio of the rare earth nanoparticles to distearate phosphatidylethanolamine-polyethylene glycol (DSPE-PEG) is 1:(1-4).

[0012] In some embodiments, the rare earth nanoparticles have a particle size of 15-20 nm.

[0013] In some embodiments, the thickness of the shell layer is 1-3 nm.

[0014] In some embodiments, the method for preparing the core layer includes: according to the core layer NaEr 1-A Tm A F4 is weighed to obtain the core layer by weighing the corresponding rare earth metal salt, sodium hydroxide and ammonium fluoride, and using a solvothermal method.

[0015] In some embodiments, the method for preparing the rare earth nanoparticles includes: weighing the corresponding rare earth metal salt, sodium hydroxide, and ammonium fluoride according to the shell layer NaLuF4, and then preparing the rare earth nanoparticles by a solvothermal method with the core layer.

[0016] The second aspect of this invention protects a method for preparing the nanocomposite material described above, comprising the following steps: mixing rare earth nanoparticles and distearate phosphatidylethanolamine-polyethylene glycol in a solvent, followed by solid-liquid separation to obtain the nanocomposite material.

[0017] A third aspect of the present invention protects the use of the nanocomposite materials described above in bio-optical imaging and / or bio-optical temperature measurement and / or the fabrication of temperature sensors.

[0018] In some embodiments, the bio-optical thermometry includes the following steps:

[0019] The dispersion of the nanocomposite material is brought into contact with the sample to be tested, and then irradiated with a near-infrared laser to obtain a first luminescence intensity at an emission peak of 1550 nm and a second luminescence intensity at an emission peak of 980 nm. The temperature of the sample to be tested is obtained by calculating the ratio of the first luminescence intensity to the second luminescence intensity.

[0020] In some embodiments, the contact method is selected from placing the sample to be tested on a dispersion of the nanocomposite material or injecting the dispersion of the nanocomposite material into the sample to be tested.

[0021] In some embodiments, the wavelength of the near-infrared laser is 700–1000 nm.

[0022] In some embodiments, the concentration of the nanocomposite material is 0.2 to 20 mg / mL, based on the total volume of the dispersion of the nanocomposite material.

[0023] A fourth aspect of the present invention protects a temperature sensor comprising the nanocomposite material described above.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1) The nanocomposite material designed in this invention has a simple structure, high temperature repeatability, good temperature stability, and the emission peak is located in the optimal imaging region (NIR-IIb) (1500-1700nm), which can significantly enhance the imaging resolution of deep tissues.

[0026] 2) The maximum relative sensitivity of the nanocomposite material of this invention for in vivo temperature detection is 3%℃. -1 This is the highest value reported to date for in vivo temperature imaging in the NIR-II region, exceeding the 2% °C reported in existing technologies. -1 This represents a 50% increase. Attached Figure Description

[0027] Figure 1 The rare earth nanoparticles NaEr in Example 1 of this invention 0.925 Y 0.075 Transmission electron microscopy image, particle size analysis histogram, scanning transmission electron microscopy, and energy-dispersive X-ray spectroscopy (EDS) elemental surface scan of F4@NaLuF4.

[0028] Figure 2 The rare earth nanoparticles NaEr in Example 1 of this invention 0.925 Y 0.075 X-ray diffraction pattern of F4@NaLuF4.

[0029] Figure 3 The NaEr nanocomposite material in Example 2 of this invention 0.925 Tm 0.075 Fourier transform infrared spectrum of F4@NaLuF4@PEG.

[0030] Figure 4 The NaEr nanocomposite material in Example 2 of this invention 0.925 Tm 0.075 Dynamic spectral scattering diagram of F4@NaLuF4@PEG.

[0031] Figure 5 The NaEr nanocomposite material in Example 3 of this invention 0.925 Tm 0.075 Fluorescence spectrum of F4@NaLuF4@PEG excited by an 808nm semiconductor laser.

[0032] Figure 6 The NaEr nanocomposite material in Example 4 of this invention0.925 Tm 0.075 Fluorescence spectra of F4@NaLuF4@PEG at different temperatures.

[0033] Figure 7 The NaEr nanocomposite material in Example 5 of this invention 0.925 Tm 0.075 Temperature-luminescence correction curve of F4@NaLuF4@PEG.

[0034] Figure 8 The NaEr nanocomposite material in Example 5 of this invention 0.925 Tm 0.075 Relative sensitivity plot of F4@NaLuF4@PEG.

[0035] Figure 9 The NaEr nanocomposite material in Example 6 of this invention 0.925 Tm 0.075 Repeated thermal cycling performance of F4@NaLuF4@PEG.

[0036] Figure 10 The NaEr nanocomposite material in Example 6 of this invention 0.925 Tm 0.075 Stability performance graph of F4@NaLuF4@PEG after multiple consecutive measurements.

[0037] Figure 11 This is a diagram of a live wound suturing procedure in Embodiment 7 of the present invention.

[0038] Figure 12 This is a schematic diagram of the live body temperature measuring device in Embodiment 7 of the present invention.

[0039] Figure 13 These are luminescent thermometer and thermal imager temperature measurements of infected and uninfected wounds in Embodiment 7 of the present invention.

[0040] Figure 14 This is a wound temperature reading obtained by thermal imaging and luminescent thermometry in Embodiment 7 of the present invention.

[0041] Figure 15 The rare earth nanoparticles NaEr in Comparative Example 1 of this invention 0.925 Y 0.075 Transmission electron microscope image of F4@NaLuF4 and NaEr 0.925 Y 0.075 Temperature-dependent fluorescence spectra and relative sensitivity plots of F4@NaLuF4@PEG.

[0042] Figure 16 The rare earth nanoparticles NaY in Comparative Example 2 of this invention 0.78 Yb 0.2 Er0.02 F4@NaLuF4 and NaY 0.775 Yb 0.2 Er 0.02 Tm 0.005 Transmission electron microscope image of F4@NaLuF4 and NaY 0.78 Yb 0.2 Er 0.02 F4@NaLuF4@PEG and NaY 0.775 Yb 0.2 Er 0.02 Tm 0.005 Temperature-dependent fluorescence spectra and relative sensitivity plots of F4@NaLuF4@PEG.

[0043] Figure 17 The rare earth nanoparticles NaEr in Comparative Example 3 of this invention 0.8 Yb 0.2 F4@NaLuF4、NaEr 0.98 Ho 0.02 Transmission electron microscope image of F4@NaLuF4 and NaEr 0.8 Yb 0.2 F4@NaLuF4@PEG、NaEr 0.98 Ho 0.02 Temperature-dependent fluorescence spectra and relative sensitivity plots of F4@NaLuF4@PEG. Detailed Implementation

[0044] In biological tissues, light scattering is significantly reduced and absorption is low in the NIR-II region (1000-1700 nm), enabling deeper tissue penetration and making it particularly suitable for deep tissue imaging. Currently, due to limitations imposed by biological tissue scattering, only luminescent probes located in the NIR-IIb region (1500-1700 nm) can provide high-resolution in vivo multipath imaging. However, most existing luminescent probes are located in the NIR-IIa region (1000-1300 nm). The NIR-IIb region (1500-1700 nm) has low autobackground fluorescence signal and weak scattering of light signals by biological tissue, making it considered the optimal optical imaging window. Therefore, there is an urgent need to develop luminescent nanoscale temperature probes with emission peaks located in the NIR-IIb region (1500-1700 nm) for high-precision temperature measurement imaging of deep tissues.

[0045] There are many types of light emission, such as electroluminescence, cathodoluminescence, radioluminescence, chemiluminescence, and photoluminescence. Photoluminescence uses light as excitation energy and emits energy in the form of light, which can be viewed as an energy conversion between excitation and emission light. This process is generally divided into three forms: up-conversion, down-conversion, and down-shifting. Down-conversion is the process of converting one short-wavelength photon into two or more long-wavelength photons. That is, after absorbing excitation light, down-conversion luminescent materials can convert high-energy incident light into low-energy emitted light, conforming to the Stokes shift law, and is also known as Stokes luminescence. Up-conversion is the process of converting two or more long-wavelength photons into one short-wavelength photon. It is the opposite of down-conversion, converting low-energy incident light into high-energy emitted light, and is also known as anti-Stokes luminescence. Down-shifting is the process of converting one short-wavelength photon into one long-wavelength photon.

[0046] In this invention, the term "Stokes" refers to the phenomenon where the energy of emitted photons is less than the energy of absorbed photons.

[0047] In this invention, the term "thermal quenching" refers to the phenomenon that when the temperature rises, the excited-state electrons of the luminescent center return to the ground state through phonon-assisted nonradiative relaxation (multiphonon emission, cross-relaxation, or charge transfer), resulting in a decrease in the probability of radiative transition and a monotonically decreasing luminescence intensity or lifetime with temperature.

[0048] In this invention, the term "luminescence-thermal enhancement" refers to the anomalous phenomenon in which, in a specific microenvironment or energy transfer path, an increase in temperature promotes the population of excited states or inhibits competing non-radiative channels, causing the luminescence intensity or quantum efficiency to increase monotonically with increasing temperature.

[0049] In this invention, the term "cross relaxation" refers to the process by which ion A transfers a portion of the energy absorbed during the transition to the adjacent ion B when ion A transitions from the excited state level E2 to the intermediate state level E1, causing ion B to transition from the ground state level G1 to the intermediate state level E1.

[0050] In this invention, the term "nonradiative relaxation" refers to the process by which excited-state electrons, without photon emission, dissipate excess energy as heat and return to a low-energy state or ground state by coupling with lattice phonons or surface / defect states.

[0051] In this invention, the term "thermal sensitivity" refers to the degree to which the luminescent properties (such as luminescence intensity, luminescence lifetime, or spectral position) of a luminescent material respond to changes in temperature. Thermal sensitivity is divided into absolute sensitivity (S... a ) and relative sensitivity (S r Absolute Sensitivity (S)a The relative sensitivity (S) refers to the absolute change in fluorescence intensity ratio (FIR) for every 1°C change in temperature. r Relative sensitivity refers to the percentage change in fluorescence intensity ratio (FIR) for every 1°C change in temperature. Relative sensitivity eliminates the influence of FIR dimensions, facilitating performance comparisons between different materials, and is the most commonly used sensitivity evaluation index. Unless otherwise specified in this application, thermal sensitivity refers to relative sensitivity.

[0052] In this invention, the term "environmental quenching-assisted down-transfer process" refers to an energy conversion mechanism in rare earth or transition metal luminescent systems where the local microenvironment (solvent, ligand, surface coordination layer, or lattice defect) enhances the energy dissipation from the excited state to a lower energy level through non-radiative relaxation channels, thereby promoting the down-transfer transition of high-energy excited photons to low-energy emitted photons, while suppressing upconversion of higher energy levels or short-wavelength luminescence.

[0053] Currently, materials with luminescence located in NIR-IIb, such as down-transfer luminescence of erbium ions, exhibit poor luminescence temperature response. For example, existing literature (Wu Y, Li F, et al. Lanthanide luminescence nanothermometer with working wavelength beyond 1500nm for cerebrovascular temperature imaging in vivo[J]. Nature Communications, 2024, 15(1):2341.) reports a relative sensitivity of 2%℃ for down-transfer fluorescent probes. -1 See details Figure 8 To address this technical problem, this application proposes a near-infrared (NIR)-IIb region luminescent and thermometric nanocomposite material, its preparation method, and its applications.

[0054] The first aspect of this invention protects a nanocomposite material for near-infrared (NIR)-IIb region luminescence and thermometry. The raw materials of the composite material include rare earth nanoparticles and distearate phosphatidylethanolamine-polyethylene glycol. The rare earth nanoparticles comprise a core layer and a shell layer covering the core layer. The general structural formula of the core layer is NaEr. 1-A Tm A F4, the general structural formula of the shell is NaLuF4, where 0≤A≤0.1.

[0055] In some implementations, A can be 0-0.07, 0.05-0.1, or 0, 0.05, 0.075, and 0.1. When A is 0.075, the relative sensitivity (S) of the nanocomposite material is...r The highest temperature can reach 3%. -1 (10℃).

[0056] The rare-earth nanoparticles and nanocomposite materials of this invention are down-transfer luminescent materials. They are produced by doping NaErF4 with Tm element and modifying it with polyethylene glycol and distearate phosphatidylethanol, resulting in a synergistic effect that gradually increases the luminescence intensity at the emission peak of 1550 nm with increasing temperature, with an increase of up to 67%. The luminescence intensity at the emission peak of 980 nm gradually decreases with increasing temperature, exhibiting a typical luminescence-thermal quenching phenomenon; however, the luminescence intensity at the emission peak of 980 nm gradually decreases with increasing temperature, exhibiting a typical luminescence-thermal enhancement phenomenon. This demonstrates a bidirectional temperature response characteristic. Therefore, by monitoring the changes in luminescence intensity at these two emission peaks, accurate temperature measurement can be achieved, and the nanocomposite materials of this invention can be used to construct temperature sensors.

[0057] In some embodiments, the nanocomposite material exhibits a decrease in luminescence intensity at the emission peak of 980 nm with increasing temperature, and an increase in luminescence intensity at the emission peak of 1550 nm with increasing temperature.

[0058] In some embodiments, the mass ratio of the rare earth nanoparticles to distearate phosphatidylethanolamine-polyethylene glycol (DSPE-PEG) is 1:(1-4), or it can be 1:(1-2.5), 1:(2-4), or 1:1, 1:2, or 1:4. In some specific embodiments, it is 1:2.

[0059] In some embodiments, the number average molecular weight of polyethylene glycol in the distearylphosphatidylethanolamine-polyethylene glycol is 2000-4000 Da, or it can be 2000-3500 Da, or 3000-4000 Da, or 2000, 3000, and 4000 Da. In some specific embodiments, it is 2000 Da. The distearylphosphatidylethanolamine-polyethylene glycol is a single-arm distearylphosphatidylethanolamine-polyethylene glycol.

[0060] In some embodiments, the rare earth nanoparticles have a particle size of 15-20 nm, or 15-18 nm, or 16-20 nm, or 15, 16, 17, 18, 19, or 20 nm. In some specific embodiments, the particle size is 17 nm.

[0061] In some embodiments, the thickness of the shell layer is 1-4 nm, or 1-2.8 nm, or 2.5-4 nm, or 1, 3, 4, 2, or 5 nm. In some specific embodiments, it is 2 nm.

[0062] In some embodiments, the method for preparing the core layer includes the following steps: based on the core layer NaEr 1-A Tm A F4 is weighed to obtain the corresponding rare earth metal salt, sodium hydroxide, and ammonium fluoride, and the core layer is obtained using a solvothermal method. In some embodiments, the preparation method of the core layer is specifically as follows:

[0063] 1) Based on the NaEr core layer 1-A Tm A F4 weighs the corresponding rare earth metal salt, sodium hydroxide, and ammonium fluoride;

[0064] 2) The rare earth metal salt and the first solvent are heated and stirred to obtain a solution;

[0065] 3) The solution, sodium hydroxide, and ammonium fluoride react to obtain the core layer.

[0066] In some embodiments, the rare earth metal salt is selected from erbium salts and thulium salts. The erbium salt is selected from one or more of erbium chloride, erbium nitrate, and erbium sulfate. The thulium salt is selected from one or more of thulium chloride, thulium nitrate, and thulium sulfate.

[0067] In some embodiments, in step 1), the first solvent is selected from at least one of oleic acid and 1-octadecene. In some specific embodiments, the first solvent is a mixture of oleic acid and 1-octadecene, wherein the volume ratio of oleic acid to 1-octadecene can be 1:(1-5), 1:(1-3), 1:(2-5), 1:2.5, 1:2, or 1:3. In one specific embodiment, it is 1:2.5.

[0068] In some embodiments, in step 2), the heating and stirring temperature is 100-140°C, or it can be 100-128°C, or 125-140°C, or it can be 100, 120, 130, or 140°C. In a specific embodiment, it is 120°C.

[0069] In some embodiments, in step 2), the heating and stirring time is 20-60 minutes, or 20-35 minutes, or 30-60 minutes, or 20, 30, 40, 50, or 60 minutes. In a specific embodiment, it is 40 minutes.

[0070] In some embodiments, in step 3), the reaction temperature is 200-400°C, or it can be 200-328°C, or it can be 300-400°C, or it can be 200, 250, 300, 350, or 400°C. In a specific embodiment, it is 300°C.

[0071] In some embodiments, in step 3), the reaction time is 30-90 minutes, or 30-50 minutes, or 40-90 minutes, or 40, 50, 60, 70, 80, or 90 minutes. In a specific embodiment, it is 60 minutes.

[0072] In some embodiments, in step 3), the sodium hydroxide and ammonium fluoride are dissolved in methanol before being added to the solution. Preferably, the process after adding the solution further includes degassing to remove methanol from the reaction system. The degassing temperature is 70-90°C, such as 80°C.

[0073] In some embodiments, after the reaction in step 3), purification and solid-liquid separation are further performed. The purification involves extraction with ethanol; the solid-liquid separation is performed by centrifugation. After solid-liquid separation, washing is performed using a reagent selected from one or both of ethanol and cyclohexane. Preferably, a mixture of ethanol and cyclohexane is used, with a volume ratio of ethanol to cyclohexane of 1:1. Those skilled in the art can adjust the ratio of ethanol to cyclohexane according to actual conditions.

[0074] In some embodiments, the preparation method of the rare earth nanoparticles includes the following steps: weighing the corresponding rare earth metal salt, sodium hydroxide, and ammonium fluoride according to the shell layer NaLuF4, and then preparing the rare earth nanoparticles by a solvothermal method with the core layer. In some embodiments, the preparation method of the rare earth nanoparticles specifically includes:

[0075] I) Weigh the corresponding rare earth metal salt, sodium hydroxide, and ammonium fluoride according to the NaLuF4 shell layer;

[0076] II) The rare earth metal salt and the second solvent are heated and stirred to obtain a solution;

[0077] III) The solution and the core layer are mixed;

[0078] IV) React the reaction product obtained in III) with sodium hydroxide and ammonium fluoride to obtain the rare earth nanoparticles.

[0079] In some embodiments, in I) or II), the rare earth metal salt is selected from lutetium salts. The lutetium salt is selected from one or more of lutetium chloride, lutetium nitrate, and lutetium sulfate.

[0080] In some embodiments, in II), the second solvent is selected from at least one of oleic acid and 1-octadecene. In some specific embodiments, the second solvent is a mixture of oleic acid and 1-octadecene, wherein the volume ratio of oleic acid to 1-octadecene can be 1:(1-5), 1:(1-3), 1:(2-5), 1:2.5, 1:2, or 1:3. In one specific embodiment, it is 1:2.5.

[0081] In some embodiments, in II), the heating and stirring temperature is 100-140°C, or it can be 100-128°C, or it can be 125-140°C, or it can be 100, 120, 130, or 140°C. In a specific embodiment, it is 120°C.

[0082] In some embodiments, in II), the heating and stirring time is 20-60 minutes, or 20-35 minutes, or 30-60 minutes, or 20, 30, 40, 50, or 60 minutes. In a specific embodiment, it is 40 minutes.

[0083] In some embodiments, the molar ratio of the core layer to the rare earth metal salt is 1:(1-2).

[0084] In some embodiments, in III), the mixing temperature is 50-150°C, or it can be 50-80°C, or it can be 70-120°C, or it can be 100-150°C, or it can be 80, 100, 120, 130, 140, or 150°C. In a particular embodiment, it is 100°C.

[0085] In some embodiments, in IV), the reaction temperature is 200-400°C, or 200-328°C, or 300-400°C, or 200, 250, 300, 350, or 400°C. In a specific embodiment, it is 300°C.

[0086] In some embodiments, in IV), the reaction time is 30-90 minutes, or 30-50 minutes, or 40-90 minutes, or 40, 50, 60, 70, 80, or 90 minutes. In a particular embodiment, it is 60 minutes.

[0087] In some embodiments, IV), after the reaction is completed, purification and solid-liquid separation are further included. The purification is performed using ethanol extraction; the solid-liquid separation is performed by centrifugation. After solid-liquid separation, washing is further included, and the washing reagent is selected from one or both of ethanol and cyclohexane. Preferably, it is a mixture of ethanol and cyclohexane, with a volume ratio of ethanol to cyclohexane of 1:1. Those skilled in the art can adjust the ratio of ethanol to cyclohexane according to actual conditions.

[0088] The nanocomposite material of this invention generates near-infrared emission peaks at 980 nm and 1550 nm under near-infrared excitation at 700–1000 nm, exhibiting a dual-response phenomenon. Therefore, a nanotemperature probe based on the bimodal emission intensity ratio can be constructed. Within the physiological temperature range, the relative sensitivity of the nanocomposite material of this invention in in vivo thermometry can reach 3% °C. -1 (10℃, that is, the relative sensitivity is 3%℃ at 10℃) -1 This is the highest reported value for temperature probes with emission peaks located in the NIR-IIb region to date. Utilizing the nanocomposite material of this invention, real-time, non-invasive temperature imaging of physiological processes within organisms is possible. Under near-infrared excitation, the nanocomposite material of this invention produces Stokes luminescence, and the down-transfer emission is efficiently redshifted to the second near-infrared optical imaging window (NIR-IIb). It exhibits extremely low photon scattering and absorption, possesses excellent biological tissue penetration capabilities, and can be used for temperature imaging of deep tissues in living organisms.

[0089] The second aspect of this invention protects a method for preparing the nanocomposite material described above, comprising the following steps: mixing the rare earth nanoparticles and distearate phosphatidylethanolamine-polyethylene glycol in a solvent, followed by solid-liquid separation to obtain the nanocomposite material.

[0090] In some embodiments, the solvent is selected from dichloromethane.

[0091] In some embodiments, the mixture further includes a step of removing organic solvents, which may include rotary evaporation, heating evaporation, vacuum drying, etc. Preferably, rotary evaporation is used to remove dichloromethane.

[0092] A third aspect of the present invention protects the use of the nanocomposite materials described above in bio-optical imaging and / or bio-optical temperature measurement and / or the fabrication of temperature sensors.

[0093] In some implementations, the intended use is not for disease diagnosis / treatment.

[0094] In some embodiments, the bio-optical thermometry includes the following steps:

[0095] The nanocomposite material is brought into contact with the sample to be tested, and irradiated with a near-infrared laser to obtain a first luminescence intensity at an emission peak of 1550 nm and a second luminescence intensity at an emission peak of 980 nm. The temperature of the sample to be tested is obtained by calculating the ratio of the first luminescence intensity to the second luminescence intensity.

[0096] In some embodiments, the contact method is selected from placing the sample to be tested on a dispersion of the nanocomposite material or injecting the dispersion of the nanocomposite material into the sample to be tested.

[0097] In some embodiments, the power of the near-infrared laser is 20–1000 mW / cm². 2 .

[0098] In some embodiments, the wavelength of the near-infrared laser is 700–1000 nm.

[0099] In some embodiments, the concentration of the nanocomposite material is 0.2–20 mg / mL, based on the total volume of the dispersion. The dispersion is obtained by dissolving the nanocomposite material in a solvent, such as water.

[0100] In some embodiments, the temperature of the sample under test can be obtained by inputting the ratio of the first luminous intensity and the second luminous intensity into a temperature calibration curve. The formula for the calibration curve is I. 1550 / 980 =2.19×10 -2 T+0.457, R 2 It is 0.99.

[0101] A fourth aspect of the present invention protects a temperature sensor comprising the nanocomposite material described above.

[0102] In some embodiments, the temperature sensor includes a near-infrared laser source, a camera, a filter, or a near-infrared spectrometer.

[0103] In some embodiments, the temperature sensor can be excited by light in the wavelength range of 700nm-1000nm and emit fluorescence, and the temperature sensor can obtain temperature data based on the detected fluorescence characteristics.

[0104] The applicant has previously studied the doping of lanthanide elements into NaYF4 matrix materials, and obtained NaErF4 matrix by doping Yb with Yb. 0.8 Yb 0.2 F4@NaLuF4 exhibits a maximum relative sensitivity of 1.6% °C; NaErF4 matrix doped with Ho yields NaErF4. 0.98 Ho 0.02F4@NaLuF4 exhibits a maximum relative sensitivity of 1.7% °C⁻¹. Furthermore, doping the NaErF4 matrix with Y and Yb yields NaY. 0.78 Yb 0.2 Er 0.02 F4@NaLuF4 exhibits a maximum relative sensitivity of 1.1% ℃⁻¹; NaY is obtained by doping NaErF4 matrix with Y, Yb, and Tm elements. 0.775 Yb 0.2 Er 0.02 Tm 0.005 F4@NaLuF4 exhibits a maximum relative sensitivity of 1% ℃⁻¹. Finally, the study found that doping NaYF4 matrix material with Tm yielded rare-earth nanoparticles NaEr. 1-A Tm A F4@NaLuF4, after being modified with distearate phosphatidylethanolamine-polyethylene glycol, exhibits the highest relative sensitivity.

[0105] This invention utilizes an erbium sublattice-mediated energy cycling strategy to enhance the relative luminescence sensitivity in the NIR-IIb region through nanoparticle microenvironment modulation. In the cyclohexane phase, erbium ions (Er...) 3+ The transfer emission at 1550 nm does not exhibit temperature-responsive properties. By modulating the intra-lattice environment, the central thulium ion (Tm) is captured by doping energy within the erbium sublattice. 3+ ), using Er 3 + and Tm 3+ Cross-relaxation (CR) between molecules imparts enhanced luminescence and thermoluminescence properties to the NIR-IIb region. Furthermore, by incorporating external environmental modulation and introducing a water molecule-mediated environmental quenching-assisted downtransfer process, Er is further enhanced. 3+ The 1550nm emission exhibits thermally enhanced luminescence properties, and makes Er... 3+ The 980nm emission exhibits luminescence thermal quenching properties. Therefore, the bidirectional response behavior of the emission peak intensities at 1550nm and 980nm with temperature can be used to construct a luminescence intensity ratio temperature probe with high temperature sensitivity. The nanocomposite material of this invention has a simple core-shell structure, with its working emission peak in the NIR-IIb region (1500-1700nm), exhibiting high relative sensitivity, up to 3% °C. -1This is the highest value reported to date. That is, for every 1°C change in temperature, the luminescence properties (such as luminescence intensity) of the nanocomposite material of this invention change by 3%. The high sensitivity indicates that the nanocomposite material of this invention can detect minute temperature changes very accurately. Therefore, the nanocomposite material of this invention provides a powerful tool for studying temperature-related physiological activities in biological tissues, filling the gap in the design of high-sensitivity temperature probes with emission peaks located in the NIR-IIb region, and is beneficial to advancing the development of high-precision thermometry imaging technology for deep tissues in vivo.

[0106] The following specific examples illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention.

[0107] Before further describing specific embodiments of the present invention, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terminology used in the embodiments of the present invention is for describing specific embodiments and not for limiting the scope of protection of the present invention; in the specification and claims of the present invention, unless otherwise expressly stated in the text, the singular forms "a", "an" and "this" include the plural forms.

[0108] When numerical ranges are given in the embodiments, it should be understood that, unless otherwise stated in the present invention, both endpoints of each numerical range and any value between the two endpoints may be selected. Unless otherwise defined, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art. In addition to the specific methods, apparatus, and materials used in the embodiments, based on the knowledge of the prior art possessed by one of ordinary skill in the art and the description of this invention, any prior art methods, apparatus, and materials similar to or equivalent to those described, apparatus, and materials in the embodiments of this invention may be used to implement the present invention.

[0109] In the following examples of this application, distearate phosphatidylethanolamine-polyethylene glycol (DSPE-PEG2000) was purchased from Shanghai Bailingwei Chemical Technology Co., Ltd.

[0110] Example 1 NaEr 0.925 Tm 0.075 Synthesis of F4@NaLuF4

[0111] 1) Based on the NaEr core layer 1-A Tm A F4 is weighed to prepare the core layer by weighing the corresponding rare earth metal salt, sodium hydroxide and ammonium fluoride.

[0112] 1-1) Mix 1 mmol of rare earth element chloride (0.925 mmol ErCl3 and 0.075 mmol TmCl3) with 6 mL of oleic acid (OA) and 15 mL of 1-octadecene (ODE) in a 100 mL three-necked flask. Heat the solution to 120 °C under nitrogen protection and maintain for 40 minutes to obtain a clear and transparent solution, and then cool to room temperature.

[0113] 1-2) Ammonium fluoride (4 mmol) and sodium hydroxide (2.5 mmol) dissolved in 10 mL of methanol were added dropwise to the solution obtained in step 1-1). The solution was then degassed at 80 °C for 30 minutes to remove methanol. Under nitrogen protection, the system was heated to 300 °C and maintained for 1 hour, then cooled to room temperature. An equal volume of anhydrous ethanol was added to the cooled solution, and the solid was obtained by centrifugation. The solid was then washed three times with an ethanol:cyclohexane (1:1 v / v) solution to obtain a core layer with oleic acid ligands on its surface. The chemical formula of the core layer is NaEr. 0.925 Tm 0.075 F4, and finally disperse the resulting core layer in 10 mL of cyclohexane (mass concentration of 10 mg / mL).

[0114] 2) Weigh the corresponding rare earth metal salts, sodium hydroxide, and ammonium fluoride according to the NaLuF4 in the shell layer, and coat the shell layer on the core layer.

[0115] 2-1) Add 1 mmol LuCl3, 6 mL oleic acid (OA), and 15 mL 1-octadecene to a three-necked flask. Then, heat to 120 °C under nitrogen protection and maintain for 40 minutes to obtain a clear and transparent solution. Then, cool to room temperature. Add 5 mL of the cyclohexane solution of the core layer obtained in step 1-2) to the cooled solution, stir at 100 °C for 20 minutes, and then cool to room temperature.

[0116] 2-2) Subsequently, ammonium fluoride (4 mmol) and sodium hydroxide (2.5 mmol) dissolved in 10 mL of methanol were added dropwise to the solution obtained in step 2-1). The solution was then degassed at 80 °C for 30 minutes to remove methanol. Under nitrogen protection, the system was heated to 300 °C and held for 1 hour, then cooled to room temperature. An equal volume of anhydrous ethanol was added to the solution, and the solid was obtained by centrifugation. The solid was then washed three times with an ethanol:cyclohexane (1:1 v / v) solution to obtain the final product with oleic acid ligands on the surface, i.e., rare earth nanoparticles. The chemical formula of the final product is NaEr. 0.925 Tm 0.075 F4@NaLuF4 (labeled as 2@OA) was then dispersed in 10 mL of cyclohexane (mass concentration of 10 mg / mL).

[0117] The results were observed using transmission electron microscopy (TEM). Figure 1 .

[0118] from Figure 1 a and Figure 1 From b, we can see that the core layer NaEr 0.925 Tm 0.075 F4 (marked as 1) and the final product NaEr 0.925 Tm 0.075 F4@NaLuF4 (labeled as 2) is composed of a large number of uniformly distributed spherical or near-spherical particles of relatively consistent size. High-resolution TEM images focusing on the outer shell show that the nanoshell is well-crystallized with a lattice spacing of 0.51 nm, corresponding to the (100) crystal plane of NaLuF4.

[0119] Particle size statistical analysis was performed on TEM images using ImageJ software, and histograms of the particle size distribution of rare earth nanoparticles and the core layer were plotted. (See image below) Figure 1 c.

[0120] from Figure 1 As can be seen from c, in the particle size analysis histogram, the core layer NaEr 0.925 Tm 0.075 The average particle size of F4 (labeled as 1) is 12.95 ± 0.71 nm, and the final product is NaEr. 0.925 Tm 0.075 The average particle size of F4@NaLuF4 (labeled as 2) is 17.22±1.23 nm, and the shell thickness is about 2 nm.

[0121] Rare earth nanoparticles were observed using a high-angle annular dark-field scanning transmission electron microscope, and elemental maps were obtained by energy-dispersive X-ray spectroscopy (EDS) surface scanning. (See attached figures.) Figure 1 d and e.

[0122] from Figure 1 From d and e, we can see that further determination of the core layer NaErF4:Tm(NaEr) of the nanocomposite material is needed. 0.925 Tm 0.075 NaLuF4 shells were successfully grown outside of F4.

[0123] The obtained core layer and final product were subjected to X-ray diffraction analysis, and the results are shown below. Figure 2 Among them, the core layer NaEr 0.925 Tm 0.075 F4 is marked as 1, NaEr 0.925 Tm 0.075 F4@NaLuF4 is marked as 2.

[0124] from Figure 2 It can be seen that the final product NaEr 0.925 Tm 0.075F4@NaLuF4 and its core layer NaEr 0.925 Tm 0.075 F4 exhibits a pure hexagonal phase.

[0125] Example 2: Distearate phosphatidylethanolamine-polyethylene glycol-modified NaEr 0.925 Tm 0.075 F4@NaLuF4 (labeled as NaEr) 0.925 Tm 0.075 F4@NaLuF4@PEG)

[0126] In this embodiment, distearate-phosphatidylethanolamine-polyethylene glycol (DSPE-PEG) modified NaEr was prepared. 0.925 Tm 0.075 F4@NaLuF4 (labeled as NaEr) 0.925 Tm 0.075 F4@NaLuF4@PEG) was used and characterized. This included the following:

[0127] 1) Weigh 20 mg of distearate phosphatidylethanolamine-polyethylene glycol (polyethylene glycol molecular weight 2000), dissolve it in 10 mL of dichloromethane, and then add 1 mL of the final product NaEr obtained in Example 1. 0.925 Tm 0.075 A cyclohexane solution of F4@NaLuF4 (mass concentration 10 mg / mL) was prepared. The mixture was stirred at room temperature for 30 minutes, and the organic solvent was removed by rotary evaporation.

[0128] 2) Subsequently, 5 mL of deionized water was added, and the solid was obtained by centrifugation. The solid was washed three times with deionized water, and finally, the washed solid was ultrasonically dispersed in 1 mL of deionized water to obtain NaEr modified with distearate phosphatidylethanolamine-polyethylene glycol. 0.925 Tm 0.075 F4@NaLuF4, also known as the nanocomposite material NaEr 0.925 Tm 0.075 F4@NaLuF4@PEG (marked as 2@PEG).

[0129] NaEr was observed using Fourier transform infrared spectroscopy. 0.925 Tm 0.075 The transformation of surface ligands before and after F4@NaLuF4 modification of distearate phosphatidylethanolamine-polyethylene glycol is as follows: Figure 3 As shown.

[0130] from Figure 3 It can be seen that NaEr 0.925 Tm 0.075F4@NaLuF4@ (labeled as 2@OA), i.e., unmodified by DSPE-PEG, exhibits a high FTIR spectrum at 1105 cm⁻¹. -1 2925cm -1 No characteristic peaks were observed at any of the locations. NaEr 0.925 Tm 0.075 F4@NaLuF4@PEG (marked as 2@PEG), also known as NaEr 0.925 Tm 0.075 F4@NaLuF4 modified with DSPE-PEG exhibits a high FTIR spectrum at 1105 cm⁻¹. -1 The characteristic peak at 2925 cm⁻¹ indicates that polyethylene glycol has been successfully modified; the FTIR spectrum at 2925 cm⁻¹... -1 The characteristic peak at [location] indicates that distearate phosphatidylethanolamine has been successfully modified. Overall, this demonstrates that the outer surface of the rare earth nanoparticles has been successfully modified with DSPE-PEG.

[0131] NaEr was determined by dynamic spectral scattering. 0.925 Tm 0.075 The particle size distribution of F4@NaLuF4@PEG (labeled as 2@PEG) is shown in the figure. Figure 4 The particle size distribution of the nanocomposite material was determined using a Malvern Zetasizer Nano ZSP nanoparticle size analyzer. During testing, the nanocomposite material was dispersed in an aqueous solution, and 1 ml of the solution was added to a quartz cuvette, which was then placed in the particle size analyzer. The testing temperature was room temperature. Results are shown below. Figure 4 .

[0132] from Figure 4 Dynamic light scattering (DLS) analysis revealed a clear single peak in the curve, indicating that the nanocomposite material is monodisperse in water and does not exhibit significant aggregation. (NaEr) 0.925 Tm 0.075 The average hydrodynamic particle size of F4@NaLuF4@PEG (labeled as 2@PEG) is 28.7 nm.

[0133] Example 3: Detection by Fluorescence Spectroscopy

[0134] In this embodiment, fluorescence spectroscopy was used to determine the NaEr obtained in Example 2. 0.925 Tm 0.075 The near-infrared emission intensity of F4@NaLuF4@PEG (labeled as 2@PEG), and in terms of NaEr 0.925 Tm 0.075 F4@PEG (labeled as 1@PEG) was used as a control.

[0135] NaEr 0.925 Tm 0.075The preparation method of F4@PEG (labeled as 1@PEG) is similar to that of NaEr. 0.925 Tm 0.075 The difference in the preparation methods of F4@NaLuF4@PEG is that, during the distearate phosphatidylethanolamine-polyethylene glycol modification, 1 mL of the core layer NaEr obtained in Example 1 is added in step 1). 0.925 Tm 0.075 F4 is a cyclohexane solution (10 mg / mL) rather than the final product NaEr. 0.925 Tm 0.075 Cyclohexane solution of F4@NaLuF4; everything else is the same as in Example 2.

[0136] The following measurements were taken using fluorescence spectroscopy:

[0137] 1) NaEr 0.925 Tm 0.075 F4@PEG (labeled as 1@PEG) and NaEr 0.925 Tm 0.075 F4@NaLuF4@PEG (labeled as 2@PEG) were dispersed in water to prepare a 10 mg / mL aqueous solution.

[0138] 2) Place 0.5 mL of the solution in a microcuvette and excite the down-transfer fluorescence using an 808 nm semiconductor laser (Ningbo Minghu, 808-3D). Place a 900 nm long-pass filter at the detection end to eliminate excitation light interference. Use a Shanghai Fuxiang Optics NIR17S series near-infrared spectrometer to detect the fluorescence. Figure 5 As shown.

[0139] from Figure 5 It can be seen that in NaEr 0.925 Tm 0.075 Epitaxial growth of an inert shell of NaLuF4 significantly enhances the near-infrared II emission intensity; compared with NaEr... 0.925 Tm 0.075 Compared to F4@PEG (labeled as 1@PEG), NaEr 0.925 Tm 0.075 The luminescence intensity of F4@NaLuF4@PEG (labeled as 2@PEG) at 1550 nm is enhanced by approximately 13 times.

[0140] Example 4: Detection by Variable Temperature Fluorescence Spectroscopy

[0141] The NaEr obtained in Example 2 was determined using variable-temperature fluorescence spectroscopy. 0.925 Tm 0.075 The fluorescence emission intensity of F4@NaLuF4@PEG (labeled as 2@PEG) dispersed in water changes with temperature. The determination method includes the following:

[0142] 1) NaEr 0.925 Tm 0.075 F4@NaLuF4@PEG (labeled as 2@PEG) was dispersed in water to prepare a 10 mg / mL aqueous solution.

[0143] 2) Take 0.5 mL of the aqueous solution from step 1) and place it in a microcuvette. Then, place the cuvette on a temperature-controlled cuvette holder and use an 808 nm semiconductor laser to excite the down-transfer fluorescence. Place a 900 nm long-pass filter (FELH0900, Thorlabs) at the detection end to eliminate excitation light interference. Heat the cuvette to 10, 20, 30, 40, 50, and 60 °C. Use a Shanghai Fuxiang Optics NIR17S series near-infrared spectrometer to obtain the luminescence intensity at 980 nm and 1550 nm at different temperatures. See [Figure showing luminescence intensity]. Figure 6 .

[0144] from Figure 6 It can be seen that the luminescence intensity at 980 nm gradually decreases with increasing temperature, exhibiting a typical thermal quenching phenomenon; while the luminescence intensity at 1550 nm gradually increases with increasing temperature, exhibiting a thermal enhancement phenomenon. The nanocomposite material of this invention utilizes DSPE-PEG surface modification to incorporate the hydrophobic cyclohexane phase NaEr... 0.925 Tm 0.075 F4@NaLuF4(Tm 3+ The dopant is transferred to the aqueous phase, and a water molecule-mediated nonradiative relaxation process occurs. 4 I 11 / 2 (Er 3+ )+ν=0(H2O)→ 4 I 13 / 2 (Er 3+ The process of ) + ν = 1(H2O) is also known as environment quenching assisted downshifting (EQAD), which effectively promotes Er 3+ of 4 I 11 / 2 → 4 I 13 / 2 Nonradiative relaxation promotes 1550nm emission (Er 3+ : 4 I 13 / 2 → 4 I 15 / 2 At the same time, reduce 980nm emission (Er 3+ : 4 I 11 / 2 → 4 I15 / 2 This results in thermal quenching at 980 nm and anomalous thermal enhancement at 1550 nm. Since the luminescence intensity of the 980 nm and 1550 nm emission peaks changes in opposite directions with temperature (i.e., bidirectional response), they can be used to construct a temperature sensor to achieve accurate temperature measurement by monitoring the relative luminescence intensity changes of these two emission peaks.

[0145] Example 5: Determination of Correction of Ex vivo Tissue

[0146] NaEr obtained in Example 2 was determined using ex vivo tissue correction assay. 0.925 Tm 0.075 The relative temperature sensitivity of F4@NaLuF4@PEG includes the following:

[0147] 5.1 Standard curve of light emission signal changing with temperature

[0148] By measuring the temperature change of the nanocomposite material under tissue coverage, the ratio of the luminescence intensity at 1550 nm and 980 nm under temperature changes was calculated. Details are as follows:

[0149] 1) NaEr 0.925 Tm 0.075 F4@NaLuF4@PEG was dispersed in water to prepare a 10 mg / mL aqueous solution. 0.5 mL of the solution was placed in a microcuvette.

[0150] 2) Using surgical scissors, a 1cm × 1cm piece of mouse skin tissue was taken from the groin of 8-week-old Balb / c mice and placed on a micro-volume cuvette. The cuvette was then placed on a temperature-controlled cuvette holder and heated to 10, 20, 30, 40, 50, and 60°C. Down-transfer fluorescence was detected using an 808nm semiconductor laser, with a 900nm long-pass filter placed at the detection end to eliminate excitation light interference. A temperature correction curve was obtained using a Shanghai Fuxiang Optics NIR17S series near-infrared spectrometer, showing the ratio of tissue-corrected 1550nm and 980nm luminescence intensities as a function of temperature. Figure 7 As shown.

[0151] from Figure 7 It can be seen that the formula for the temperature correction curve is I. 1550 / 980 =2.19×10 -2 T+0.457, R 2 It is 0.99.

[0152] Furthermore, the relative sensitivity is calculated using the following formula:

[0153]

[0154] Where Sr Relative sensitivity (unit: %℃) -1 Ratio is the ratio of the luminous intensity at 1550 nm to that at 980 nm, and T is the temperature. Relative sensitivity refers to the percentage change in the luminous intensity ratio (FIR) for every 1°C change in temperature.

[0155] Its relative sensitivity can be calculated, such as Figure 8 As shown.

[0156] from Figure 8 It is known that the maximum relative sensitivity can reach 3%℃ within the physiological temperature range (10-60℃). -1 (10℃).

[0157] Example 6 NaEr 0.925 Tm 0.075 Thermometric stability of F4@NaLuF4@PEG

[0158] The NaEr obtained in Example 2 0.925 Tm 0.075 F4@NaLuF4@PEG was dispersed in water to prepare a 10 mg / mL aqueous solution.

[0159] 0.5 mL of solution was placed in a micro-volume cuvette, and mouse skin tissue was covered on the cuvette. The cuvette was then placed in a variable-temperature cuvette holder, and the fluorescence was transferred under excitation by an 808 nm semiconductor laser. A 900 nm long-pass filter was placed at the detection end to eliminate excitation light interference. The luminescence intensity was measured using a NIR17S series near-infrared spectrometer from Shanghai Fuxiang Optics.

[0160] The ratio of luminescence intensity at 1550 nm and 980 nm was measured under thermal cycling at 10 °C and 60 °C. The thermal cycling was repeated 7 times, and the results are shown below. Figure 9 .

[0161] from Figure 9 It can be seen that under repeated thermal cycles, I 1550 / 980 The ratio of luminescence intensity is stable. At 10°C, the ratio is approximately 1; at 60°C, the ratio is approximately 2, exhibiting a similar fluctuation pattern to that at 10°C. This indicates that the nanocomposite material of the present invention has good thermal stability, maintaining its luminescence properties unchanged under temperature changes, and exhibits high repeatability.

[0162] At room temperature (25℃), the ratio of luminescence intensity at 1550nm and 980nm was measured 40 times consecutively. Figure 10 As shown.

[0163] from Figure 10It can be seen that the stability is good after 40 consecutive measurements.

[0164] Example 7 NaEr 0.925 Tm 0.075 F4@NaLuF4@PEG is used for in vivo temperature imaging and temperature detection.

[0165] Eight-week-old Balb / c mice were used for wound closure modeling. First, hair was removed from the groin area of ​​the mice using depilatory cream. Then, a 5mm × 5mm area of ​​skin tissue was harvested using surgical scissors. A 5mm deep wound was then created using a 5mm diameter mouse skin punch. NaEr 0.925 Tm 0.075 An aqueous solution of F4@NaLuF4@PEG (20 mg / mL, 10 μL) and an E. coli suspension (10 μL) 8 CFU / mL (10 μL) was applied dropwise to the wound area. Finally, the wound skin was sealed with biological tissue adhesive (3M Vetbon, 3M Company). Figure 11 One hour later, optical imaging was performed on the wound area. This was part of the infection group.

[0166] At the same time, NaEr was administered to the injury-causing mice. 0.925 Tm 0.075 An aqueous solution of F4@NaLuF4@PEG (20 mg / mL, 10 μL) was used, but no E. coli suspension was added as a control, i.e., the uninfected group.

[0167] A schematic diagram of the live body temperature measurement device is shown below. Figure 12 As shown. The workflow of the luminescence thermometry is as follows: a laser emits an 808nm laser to excite the nanocomposite material in the wound area; the nanocomposite material emits a near-infrared II emission signal after excitation; a near-infrared II camera receives these emission signals and converts them into two-dimensional image data. The near-infrared II camera uses a 900nm long-pass filter, a 1050nm short-pass filter, and a 1500nm long-pass filter to acquire images at the emission peaks of 980nm and 1550nm. Then, I is calculated. 1550 / 980 The ratio of luminous intensity was calculated and input into the temperature correction curve obtained in Example 5 to obtain the temperature value of the wound area. The results are shown in [the original text]. Figure 14 .

[0168] Meanwhile, an infrared thermal imager was used to monitor changes in wound temperature.

[0169] Temperature maps of infected wounds obtained by infrared thermal imager (thermal imager) and luminescent thermometry are shown below. Figure 13 Where A is the luminescent thermograph and B is the infrared thermal imager thermograph; the temperature readings are shown in [reference needed]. Figure 14 .

[0170] from Figure 13 It can be seen that the temperature measured by luminescent thermometry (Figure A) is higher than that measured by infrared thermal imager (B), indicating that luminescent thermometry can detect the minute temperature changes caused by E. coli infection, while thermal imager temperature measurement is difficult to reflect wound infection signals.

[0171] from Figure 14 The results show that the average wound temperature in the infected group was 38.3℃, while the average wound temperature in the uninfected group was 37.1℃. The infrared thermal imager shows that the average wound temperature in the infected group was 36.8℃, while the average wound temperature in the uninfected group was 35.3℃. Because the infrared thermal imager can only acquire the surface temperature of an object, it displays a lower temperature reading.

[0172] Example 8

[0173] The difference between Example 8 and Example 1 is that 1 mmol ErCl3 is used to replace 0.925 mmol ErCl3 and 0.075 mmol TmCl3 in step 1-1) of Example 1. All other steps are the same as in Example 1, resulting in NaEr dispersed in cyclohexane. 0.925 Y 0.075 F4@NaLuF4 (mass concentration of 10 mg / mL). Then, the same steps as in Example 2 were used to modify distearate phosphatidylethanolamine-polyethylene glycol to obtain NaErF4@NaLuF4@PEG.

[0174] The relative sensitivity of the nanocomposite material obtained in this embodiment was measured using the same method as in Example 5, and the maximum value was taken. The results are shown in Table 1.

[0175] Example 9

[0176] The difference between Example 9 and Example 1 is that Example 9 uses 0.95 mmol ErCl3 and 0.05 mmol TmCl3 instead of 0.925 mmol ErCl3 and 0.075 mmol TmCl3 in step 1-1) of Example 1. All other steps are the same as in Example 1, resulting in NaEr dispersed in cyclohexane. 0.95 Tm 0.05 F4@NaLuF4 (mass concentration of 10 mg / mL). Then, the distearate phosphatidylethanolamine-polyethylene glycol was modified using the same steps as in Example 2 to obtain NaEr. 0.95 Tm 0.05 F4@NaLuF4@PEG.

[0177] The maximum relative sensitivity of the nanocomposite material obtained in this embodiment was measured using the same method as in Example 5, and the maximum value was taken. The results are shown in Table 1.

[0178] Example 10

[0179] The difference between Example 10 and Example 1 is that 0.9 mmol ErCl3 and 0.1 mmol TmCl3 are used instead of 0.925 mmol ErCl3 and 0.075 mmol TmCl3 in step 1-1) of Example 1. All other aspects are the same as in Example 1, resulting in NaEr dispersed in cyclohexane. 0.9 Tm 0.1 F4@NaLuF4 (mass concentration of 10 mg / mL). Then, the distearate phosphatidylethanolamine-polyethylene glycol was modified using the same steps as in Example 2 to obtain NaEr. 0.9 Tm 0.1 F4@NaLuF4@PEG.

[0180] The maximum relative sensitivity of the nanocomposite material obtained in this embodiment was measured using the same method as in Example 5, and the maximum value was taken. The results are shown in Table 1.

[0181] Table 1

[0182] Rare earth nanoparticles Particle size (nm) Shell thickness (nm) <![CDATA[Maximum relative sensitivity (S r max, %°C -1 )]]> Example 1 <![CDATA[NaEr 0.925 Tm 0.075 F4@NaLuF4]]> 17.22 2.1 3.0 Example 8 <![CDATA[NaEr 0.95 Tm 0.05 F4@NaLuF4]]> 20.42 2.9 2.1 Example 9 <![CDATA[NaErF4@NaLuF4]]> 18.56 2.0 1.1 Example 10 <![CDATA[NaEr 0.9 Tm 0.1 F4@NaLuF4]]> 16.10 1.8 1.9

[0183] Comparative Example 1 NaEr 0.925 Y 0.075 F4@NaLuF4

[0184] The difference between Comparative Example 1 and Example 1 is that 0.925 mmol ErCl3 and 0.075 mmol TmCl3 in step 1-1) of Example 1 are replaced with 0.925 mmol ErCl3 and 0.075 mmol YCl3, respectively. All other aspects are the same as in Example 1, resulting in NaEr dispersed in cyclohexane. 0.925 Y 0.075 F4@NaLuF4 (mass concentration of 10 mg / mL). Then, the distearate phosphatidylethanolamine-polyethylene glycol was modified using the same steps as in Example 2 to obtain NaEr. 0.925 Y 0.075 F4@NaLuF4@PEG.

[0185] NaEr prepared in cyclohexane according to Comparative Example 1 0.925 Y 0.075 The temperature-dependent fluorescence spectroscopy results of F4@NaLuF4 are shown in the figure. Figure 15 a. NaEr prepared in cyclohexane as described in Example 1 0.925 Tm 0.075 The temperature-dependent fluorescence spectroscopy results of F4@NaLuF4 are shown in the figure. Figure 15Figure b shows the mechanism diagram drawn using Adobe Illustrator 2024. The NaEr prepared in Comparative Example 1... 0.925 Y 0.075 The temperature-dependent fluorescence detection results of F4@NaLuF4@PEG are shown in the figure. Figure 15 In section c, a mechanism diagram was created using Adobe Illustrator 2024. (For...) Figure 15 Figures a, b, and c in the diagram, and Figure 6 Normalization was performed, see Figure 15 d.

[0186] NaEr dispersed in cyclohexane 0.925 Y 0.075 F4@NaLuF4 (or NaEr) 0.925 Tm 0.075 The temperature-dependent fluorescence spectrometry method for detecting F4@NaLuF4 was as follows: Take 0.5 mL of 10 mg / mL NaEr... 0.925 Y 0.075 F4@NaLuF4 (or NaEr) 0.925 Tm 0.075 A cyclohexane solution of F4@NaLuF4 was placed in a micro-volume cuvette, which was then placed on a temperature-controlled cuvette holder. The remaining steps were the same as step 2 in Example 4.

[0187] from Figure 15 As can be seen from a, within the temperature range of 10-60℃, NaEr dispersed in cyclohexane 0.925 Y 0.075 The luminescence intensity of F4@NaLuF4 at 1550 nm has no temperature response.

[0188] from Figure 15 As can be seen from b, the nanocomposite material NaEr of this application 0.925 Tm 0.075 The luminescence intensity of F4@NaLuF4 at 1550 nm exhibits a significant temperature response, and NaEr... 0.925 Tm 0.075 The luminescence intensity of F4@NaLuF4 at 1550 nm increased by 17%, and this enhancement process is denoted as Effect 1. The increase in luminescence intensity is calculated by subtracting the luminescence intensity at 1550 nm at 10 °C from the luminescence intensity at 1550 nm at 60 °C, and then dividing by the luminescence intensity at 1550 nm at 10 °C. Its mechanism involves the introduction of energy-harvesting centers Tm through lattice environment modulation. 3+ Under 808nm excitation, Er 3+ : 4 I 15 / 2 ground state electron transition to Er3+ : 4 I 9 / 2 Excited state, Tm 3+ : 3 H4 level captures from Er 3+ : 4 I 9 / 2 The energy of the excited state, this process is a phonon-assisted energy transfer (PAT) process, i.e., Er 3+ : 4 I 9 / 2 →Tm 3+ : 3 H4. Then Tm 3+ The captured excited-state energy is transferred back to Er via a cross relaxation (CR) process. 3+ That is, [Tm] 3+ ( 3 H4); Er 3+ ( 4 I 15 / 2 )]→[Er 3+ ( 4 I 13 / 2 );Tm 3+ ( 3 F4)], promoting Er 3+ : 4 I 13 / 2 The electronic configuration of the excited state endows Er 3+ : 4 I 13 / 2 Energy level temperature response capability.

[0189] NaEr 0.925 Y 0.075 The luminescence intensity was measured by dispersing F4@NaLuF4@PEG in water, and the temperature-dependent fluorescence detection was the same as in Example 4. The results are shown below. Figure 15 c.

[0190] from Figure 15 As can be seen from c, within the temperature range of 10-60℃, NaEr 0.925 Y 0.075 The F4@NaLuF4@PEG material exhibits a 24% increase in luminescence intensity at 1550 nm in aqueous phase; this enhancement is denoted as Effect Two. The calculation method for the luminescence intensity enhancement is the same as above. Its mechanism involves regulation of the external environment (i.e., the NaEr in the cyclohexane phase). 0.925 Y 0.075 F4@NaLuF4, after being modified with DSPE-PEG and dispersed in water, introduces luminescence quenching centers (H2O). Under 808 nm excitation, Er... 3+ :4 I 15 / 2 ground state electron transition to Er 3+ : 4 I 9 / 2 The excited state then undergoes a multiphonon relaxation (MPR) process, i.e., Er 3+ : 4 I 9 / 2 →Er 3+ : 4 I 11 / 2 As the temperature rises, Er 3+ : 4 I 11 / 2 The energy transfer process between the energy level and the ground state vibrational energy level of H2O is intensified, that is... 4 I 11 / 2 (Er 3+ )+ν=0(H2O)→ 4 I 13 / 2 (Er 3+ )+ν=1(H2O), promoting Er 3+ : 4 I 13 / 2 The electronic configuration of the excited state endows Er 3+ : 4 I 13 / 2 Energy level temperature response capability.

[0191] from Figure 15 As can be seen from d, within the temperature range of 10-60℃, NaEr dispersed in cyclohexane 0.925 Y 0.075 F4@NaLuF4 material (labeled as γ-cyclohexane in the figure) exhibits no temperature-responsive properties. Introducing Effect 1 (i.e., Tm doping) (Tm-cyclohexane) results in enhanced luminescence at 1550 nm, with a 17% increase in intensity. Furthermore, introducing Effect 2 (DSPE-PEG modification) (γ-water) further enhances luminescence at 1550 nm, resulting in a 24% increase in intensity. The NaEr material prepared in Example 2 of this application... 0.925 Tm 0.075 F4@NaLuF4@PEG showed a 67% increase in luminescence intensity at 1550 nm in the aqueous phase within the temperature range of 10-60℃.

[0192] In summary, traditional cyclohexane-phase erbium sublattice materials (NaEr) 0.925 Y 0.075F4@NaLuF4 does not exhibit temperature-responsive properties at 1550 nm. However, by using either Effect 1 (erbium doping) or Effect 2 (modification with DSPE-PEG), it can be endowed with temperature-responsive emission at 1550 nm, and the temperature-responsive emission at 1550 nm can be further enhanced, i.e., the emission intensity increases by 67%, which is much greater than the sum of 17% (Effect 1) and 24% (Effect 2).

[0193] Comparative Example 2NaY 0.78 Yb 0.2 Er 0.02 F4@NaLuF4 and NaY 0.775 Yb 0.2 Er 0.02 Tm 0.005 Synthesis of F4@NaLuF4:

[0194] The applicant also studied the changes in the transfer spectrum of traditional NaYF4 matrix materials at different temperatures.

[0195] The difference between Comparative Example 2 and Example 1 is that Comparative Example 2 uses 0.78 mmol YCl3, 0.02 mmol ErCl3, and 0.2 mmol YbCl3; or, it uses NaY. 0.775 Yb 0.2 Er 0.02 Tm 0.005 F4, 0.775 mmol YCl3, 0.2 mmol YbCl3, 0.02 mmol ErCl3, and 0.05 mmol TmCl3 replaced the 0.925 mmol ErCl3 and 0.075 mmol TmCl3 in step 1-1) of Example 1, while the rest were the same as in Example 1, to obtain NaY 0.78 Yb 0.2 Er 0.02 F4@NaLuF4、NaY 0.775 Yb 0.2 Er 0.02 Tm 0.005 F4@NaLuF4. Then, using the same steps as in Example 2, distearate phosphatidylethanolamine-polyethylene glycol was modified to obtain NaY. 0.78 Yb 0.2 Er 0.02 F4@NaLuF4@PEG、NaY 0.775 Yb 0.2 Er 0.02 Tm 0.005 F4@NaLuF4@PEG.

[0196] NaY 0.78 Yb 0.2 Er 0.02The scanning electron microscope image of F4@NaLuF4 is shown below. Figure 16 a, NaY 0.78 Yb 0.2 Er 0.02 The results of temperature-dependent fluorescence spectroscopy detection of F4@NaLuF4@PEG dispersed in water are shown below. Figure 16 c, NaY 0.78 Yb 0.2 Er 0.02 The relative sensitivity of F4@NaLuF4@PEG is shown in [link to relevant data]. Figure 16 e.

[0197] NaY 0.775 Yb 0.2 Er 0.02 Tm 0.005 The scanning electron microscope image of F4@NaLuF4 is shown below. Figure 16 b, NaY 0.775 Yb 0.2 Er 0.02 Tm 0.005 Results of temperature-dependent fluorescence spectroscopy for the dispersion of F4@NaLuF4@PEG in water Figure 16 d, NaY 0.775 Yb 0.2 Er 0.02 Tm 0.005 F4@NaLuF4@PEG relative sensitivity Figure 16 f in the middle.

[0198] from Figure 16 From e and f, we know that NaY 0.775 Yb 0.2 Er 0.02 Tm 0.005 F4@NaLuF4 has low erbium ion doping (2%), which is relatively better than highly erbium ion doped structures (erbium sublattice materials, i.e., the NaEr obtained in Example 1 of this application). 0.925 Tm 0.075 F4@NaLuF4) shows a relatively low relative sensitivity, approximately 1% °C⁻¹; while NaY 0.78 Yb 0.2 Er 0.02 The relative sensitivity of F4@NaLuF4 is approximately 1.1%℃⁻¹.

[0199] Comparative Example 3NaEr 0.8 Yb 0.2 F4@NaLuF4、NaEr 0.98 Ho 0.02 Synthesis of F4@NaLuF4:

[0200] The difference between Comparative Example 3 and Example 1 is that 0.8 mmol ErCl3 and 0.2 mmol YbCl3 or 0.98 mmol ErCl3 and 0.02 mmol HoCl3 are used instead of 0.925 mmol ErCl3 and 0.075 mmol TmCl3 in step 1-1) of Example 1, and Yb or Ho is used instead of Tm doping (that is, YbCl3 or HoCl3 is used instead of TmCl3). All other aspects are the same as in Example 1, and NaEr is obtained respectively. 0.8 Yb 0.2 F4@NaLuF4、NaEr 0.98 Ho 0.02 F4@NaLuF4. Then, using the same steps as in Example 2, distearate phosphatidylethanolamine-polyethylene glycol was modified to obtain NaEr. 0.925 Y 0.075 F4@NaLuF4@PEG、NaEr 0.98 Ho 0.02 F4@NaLuF4@PEG.

[0201] NaEr 0.8 Yb 0.2 The scanning electron microscope image of F4@NaLuF4 is shown below. Figure 17 a, NaEr 0.8 Yb 0.2 The results of temperature-dependent fluorescence spectroscopy detection of F4@NaLuF4@PEG dispersed in water are shown below. Figure 17 For the relative sensitivity of c, see [reference]. Figure 17 e.

[0202] NaEr 0.98 Ho 0.02 The scanning electron microscope image of F4@NaLuF4 is shown below. Figure 17 b, NaEr 0.98 Ho 0.02 The results of temperature-dependent fluorescence spectroscopy detection of F4@NaLuF4@PEG dispersed in water are shown below. Figure 17 For the relative sensitivity, see [reference d]. Figure 17 f in the middle.

[0203] from Figure 17 As can be seen from Figure e and Figure f, NaEr 0.98 Ho 0.02 F4@NaLuF4@PEG or NaEr 0.8 Yb 0.2 The relative sensitivity of F4@NaLuF4@PEG is higher than that of the low-erbium-doped material (i.e., NaY in Comparative Example 2). 0.775 Yb 0.2 Er 0.02 Tm 0.005F4@NaLuF4), but lower than the NaEr synthesized in Example 2. 0.925 Tm 0.075 F4@NaLuF4@PEG. The reason is energy level mismatch, Yb 3+ Or Ho 3+ None of them can be like Tm 3+ Similarly, with Er 3+ The same phonon-assisted energy transfer process and subsequent interionic cross-relaxation process occur, resulting in lower thermal sensitivity, or relative sensitivity.

[0204] The above embodiments are for illustrating the implementation schemes disclosed in this invention and should not be construed as limiting the invention. Furthermore, various modifications listed herein, as well as variations in the methods and compositions of the invention, will be apparent to those skilled in the art without departing from the scope and spirit of the invention. Although the invention has been specifically described in conjunction with various specific preferred embodiments, it should be understood that the invention should not be limited to these specific embodiments. In fact, various modifications as described above that are obvious to those skilled in the art to obtain the invention should be included within the scope of this invention.

Claims

1. A nanocomposite material for near-infrared (NIR)-IIb region luminescence and thermometry, characterized in that, The raw materials of the nanocomposite material include rare earth nanoparticles and distearate phosphatidylethanolamine-polyethylene glycol. The rare earth nanoparticles include a core layer and a shell layer covering the core layer. The general structural formula of the core layer is NaEr. 1-A Tm A F4, the general structural formula of the shell is NaLuF4, where 0≤A≤0.

1.

2. The nanocomposite material as described in claim 1, characterized in that, The mass ratio of the rare earth nanoparticles to distearate phosphatidylethanolamine-polyethylene glycol is 1:(1-4); And / or, the particle size of the rare earth nanoparticles is 15-20 nm; And / or, the thickness of the shell is 1-3 nm.

3. The nanocomposite material as described in claim 1, characterized in that, The nanocomposite material exhibits a decrease in luminescence intensity at the emission peak of 980 nm with increasing temperature, and an increase in luminescence intensity at the emission peak of 1550 nm with increasing temperature.

4. The nanocomposite material as described in claim 1, characterized in that, The method for preparing the core layer includes: according to the core layer NaEr 1-A Tm A F4 is prepared by weighing the corresponding rare earth metal salt, sodium hydroxide, and ammonium fluoride, and then using a solvothermal method.

5. The nanocomposite material as described in claim 4, characterized in that, The method for preparing the rare earth nanoparticles includes: weighing the corresponding rare earth metal salt, sodium hydroxide, and ammonium fluoride according to the shell layer NaLuF4, and then preparing them with the core layer by a solvothermal method.

6. The method for preparing the nanocomposite material according to any one of claims 1-5, characterized in that, The process includes the following steps: rare earth nanoparticles and distearate phosphatidylethanolamine-polyethylene glycol are mixed in a solvent, followed by solid-liquid separation to obtain the nanocomposite material.

7. Use of the nanocomposite material as described in any one of claims 1-5 in bio-optical imaging and / or bio-optical temperature measurement and / or in the fabrication of temperature sensors.

8. The use as described in claim 7, characterized in that, The bio-optical thermometry includes the following steps: The dispersion of the nanocomposite material is brought into contact with the sample to be tested, and near-infrared laser is used to irradiate it to obtain a first luminescence intensity at an emission peak of 1550 nm and a second luminescence intensity at an emission peak of 980 nm. The temperature of the sample to be tested is obtained by calculating the ratio of the first luminescence intensity to the second luminescence intensity.

9. The use as described in claim 8, characterized in that, The wavelength of the near-infrared laser is 700–1000 nm; And / or, based on the total volume of the dispersion of the nanocomposite material, the concentration of the nanocomposite material is 0.2 to 20 mg / mL.

10. A temperature sensor, characterized in that, It includes the nanocomposite material as described in any one of claims 1-5.

Citation Information

Patent Citations

  • A multi-response nano-temperature detection probe, its preparation method and application

    CN113930235B